Transverse myelopathy and radiculomyelopathy associated with pulmonary atypical Mycobacterium infections. Issue 2 (1st February 2001) - White, V L C; Al-Shahi, R; Gamble, E; Brown, P; Davison, A G
Abstract : Myelopathy is a well recognised but rare association with Mycobacterium tuberculosis infection, but has not been described with atypical mycobacteria. We report two cases of disabling myelopathy in association with pulmonary infection by Mycobacterium kansasii and Mycobacterium malmoense ; the myelopathy is presumed to be a para-infectious phenomenon.